2023
DOI: 10.3390/cimb45100514
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E Exerts Anti-Proliferative Activity via Promoting p62-Dependent Apoptosis in Human Non-Small-Cell Lung Cancer A549 Cells

Han-Lin Hsu,
Bo-Jyun Lin,
Yu-Chen Lin
et al.

Abstract: EGFR tyrosine kinase inhibitors (TKIs) are the first-line treatment for advanced EGFR-mutated non-small-cell lung cancer (NSCLC). However, NSCLC patients with wild-type EGFR and KRAS mutation are ineligible for EGFR-TKIs. Therefore, the discovery of new therapeutic agents is urgently needed for NSCLC patients who cannot receive targeted therapies. Natural products possess tremendous chemical diversity and have been extensively investigated for their anticancer activity. In this study, we found that Cucurbitaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Cucurbitacin, triterpenoid including cucurbitacin B and cucurbitacin E, are triterpenoids from the cucurbitaceae family Cucumis melo L., which have therapeutic effects on a wide range of tumors ( Hong T et al, 2023 ; Hsu HL et al, 2023 ; Yang Y et al, 2023 ). Huang JL et al (2023) found that cucurbitacin B (0.005, 0.01, 0.05, 1, 5, 10, 20, 40, 100 μM for 48 h) inhibited the proliferation and induced apoptosis of CRC cells HT-29 and SW620 by concentration-dependently increasing the protein expression of p-PERK, p-eIF2α, ATF4, IRE1α and XBP1.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%
“…Cucurbitacin, triterpenoid including cucurbitacin B and cucurbitacin E, are triterpenoids from the cucurbitaceae family Cucumis melo L., which have therapeutic effects on a wide range of tumors ( Hong T et al, 2023 ; Hsu HL et al, 2023 ; Yang Y et al, 2023 ). Huang JL et al (2023) found that cucurbitacin B (0.005, 0.01, 0.05, 1, 5, 10, 20, 40, 100 μM for 48 h) inhibited the proliferation and induced apoptosis of CRC cells HT-29 and SW620 by concentration-dependently increasing the protein expression of p-PERK, p-eIF2α, ATF4, IRE1α and XBP1.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%